Edukasi Tentang Pencegahan dan Pengendalian Hipertensi pada Masyarakat di Desa Lemo Ape Kecamatan Palakka Kabupaten Bone - Megawati Sibulo; Alfian Mas’ud; Najman Najman; A. Sri Ulfi Nofriati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypertension is one of the most prevalent non-communicable diseases in society. Hypertension is known as a silent killer and the leading cause of death in the world because this disease can cause death without any symptoms. Therefore, it is important to provide education in the form of health counseling to the community to reduce mortality rates by changing daily lifestyles to avoid hypertension. The purpose of this community service is to provide information to increase public knowledge about efforts to prevent and control hypertension in Lemo Ape Village, Palakka District, Bone Regency. The community service activity in the form of health education for community leaders was conducted on Saturday 7 September 2024 from 08:00 to 09:00 WITA. The results of this community service show that from several questions posed, it is evident that the community's understanding of hypertension is still very minimal, especially regarding how to properly prevent it, the causative factors, and the appropriate treatment to lower blood pressure.